Pelatihan Keterampilan Dasar Laboratorium untuk Meningkatkan Keterampilan Proses Sains Siswa SMA - Rahma Widiantie; Ina Setiawati; Ilah Nurlaelah; Lela Lela (ARDHI : Jurnal Pengabdian Dalam Negri, 2025)
The implementation of Biology learning in senior high schools still faces various challenges, particularly the limitations of laboratory facilities and the low level of students’ science process skills(KPS). KPS  is an essential ability that supports conceptual understanding and critical thinking development through practical activities. This community service program aimed to improve students’ basic laboratory skills and KPS through hands-on training. The program was conducted at the Biology Education Laboratory of the Faculty of Teacher Training and Education, Kuningan University, involving students from SMAN 1 Ciwaru. The methods included socialization, laboratory equipment training, preparation of practical materials, animal dissection training, application of virtual laboratory technology, and mentoring and evaluation sessions. The results showed a significant improvement in students’ abilities to use laboratory tools, prepare materials, and perform experiments according to scientific procedures. Before the training, only 32% of students were able to use laboratory equipment correctly, while after the training, this increased to 84%. The average scores for observation, measurement, data interpretation, and scientific communication also improved significantly. Furthermore, a satisfaction survey revealed an average score of 4.6 out of 5, with 92% of participants stating that the activity was very beneficial. This program proved effective in enhancing students’ basic laboratory and science process skills, providing meaningful, applicable, and sustainable science learning experiences. Keywords: : training, basic skills, laboratory, science process skills, biology.